A novel case–control design to estimate the extent of over‐diagnosis of breast cancer due to organised population‐based mammography screening. Issue 6 (18th August 2014) - Beckmann, Kerri R.; Lynch, John W.; Hiller, Janet E.; Farshid, Gelareh; Houssami, Nehmat; Duffy, Stephen W.; Roder, David M.
<x xml:space="preserve">Abstract</x> Debate about the extent of breast cancer over‐diagnosis due to mammography screening has continued for over a decade, without consensus. Estimates range from 0 to 54%, but many studies have been criticized for having flawed methodology. In this study we used a novel study design to estimate over‐diagnosis due to organised mammography screening in South Australia (SA). To estimate breast cancer incidence at and following screening we used a population‐based, age‐matched case–control design involving 4, 931 breast cancer cases and 22, 914 controls to obtain OR for yearly time intervals since women's last screening mammogram. The level of over‐diagnosis was estimated by comparing the cumulative breast cancer incidence with and without screening. The former was derived by applying ORs for each time window to incidence rates in the absence of screening, and the latter, by projecting pre‐screening incidence rates. Sensitivity analyses were undertaken to assess potential biases. Over‐diagnosis was estimated to be 8% (95%CI 2–14%) and 14% (95%CI 8–19%) among SA women aged 45 to 85 years from 2006–2010, for invasive breast cancer and all breast cancer respectively. These estimates were robust when applying various sensitivity analyses, except for adjustment for potential confounding assuming higher risk among screened than non‐screened women, which reduced levels of over‐diagnosis to 1% (95%CI 5–7%) and 8% (95%CI 2–14%) respectively when incidence rates for screening participants were adjusted by 10%. Our results indicate that the level of over‐diagnosis due to mammography screening is modest and considerably lower than many previous estimates, including others for Australia.